Helping Hand or Grabbing Hand? Central vs. Local Government Shareholders in Chinese Listed Firms - Cheung, Yan-Leung; Rau, P. Raghavendra; Stouraitis, Aris (Review of Finance, 2010)
Abstract We analyze related party transactions between Chinese publicly listed firms and their state-owned shareholders to examine whether companies benefit or lose from the presence of government shareholders and politically connected directors. Minority shareholders seem to be expropriated in firms controlled by local governments, firms with a large proportion of local government directors on their board, firms without central government directors, and firms in provinces where local government bureaucrats are less likely to be prosecuted for corruption. In contrast, firms controlled by the central government (or having central government affiliated directors), benefit in related party transactions with their government parents.